Pemahaman Bacaan Siswa SMP Alikhlas Melalui Literasi Baca dan Tulis - Priyono Priyono; Ibnu Fiqhan Muslim; Sigit Widiyarto (Jurnal Ilmiah Wahana Pendidikan, 2022)
Reading comprehension in students is an important and strategic ability. Reading comprehension is closely related to reading and writing literacy. Mastery of reading comprehension in students is also related to all subjects at school, because students who are able to understand reading well will be able to absorb all the knowledge information that is read. This study aims to describe the literacy process that can improve the reading comprehension ability of students at Alikhlas Junior High School Bekasi. The method used is descriptive qualitative method. Data collection was done by observation, interviews, and documentation. The number of respondents was 8 students of class VII SMP Al Ikhlas. The results showed that students who had good reading comprehension were able to complete school assignments well. Children who have high reading comprehension tend to have good literacy skills